ANALISIS PENGARUH DEFISIT FISKAL TERHADAP PERTUMBUHAN EKONOMI INDONESIA - AGHSILNI AGHSILNI; DARVI MAILISA PUTRI (Maqdis: Jurnal Kajian Ekonomi Islam, 2020)
This study aims to know and analyze: the influence of fiscal deficit on economic growth of Indonesia in the long and short run. The data in this study are time series data from 1988 to 2019 and using cointegration test and Vector Error Correction Model (VECM). The result of the research show that (1) fiscal deficit, FDI and inflation have a significant effect on economic growth. The fiscal deficit has a positive effect, meanwhile FDI and inflation have a negative effect on economic growth. (2) In the short run, fiscal deficit in lag 1 and FDI in lag 1 and lag 2 have a significant effect on economic growth, but inflation have no significant effect both in lag 1 and lag 2. However, in the long run, economic growth will return to its equilibrium.